Indian foreign direct investments in Africa: a geographical perspective - Anwar Mohammad Amir (Bulletin of Geography. Socio-Economic Series, 2014)
Foreign direct investments (FDI) into Africa from developing economies have grown substantially over the past decade. While the focus of the enquiry among the geographers has been the rise of Chinese investments in Africa, India has become an important ‘Asian driver’ within the ‘new scramble for Africa’. This article highlights the geography of Indian involvement in Africa in terms of its growing scale, new patterns and the emerging complex structure of Indian investments. The article finds that the nature of India-Africa trade relationship mirrors colonial trade relationships between India and the Great Britain. The Indian investments in Africa are resource- oriented and fused with geopolitical dynamics, driven by capitalistic agendas.